COVID-19 UNCERTAINTIES AND PAKISTAN’S ECONOMIC PROBLEMS DURING THE PANDEMIC - Lakhan, Ghulam Rasool; Soomro, Bahadur Ali; Channa, Amanullah; Jameel, Ifrah; Ahmed, Shabbir (The journal of contemporary issues in business and government, 2021)
In the present era, the COVID-19 appeared as a dangerous virus that ruined all most all economies of the globe. The present paper attempts to review the economic problems and uncertainties that affected the Pakistani economy in the COVID-19 pandemic waves. The study is based on a desk review. The data are derived from reliable sources to achieve the purpose of the study. The study's findings suggest that the economy of Pakistan has confronted significant challenges in the pandemic. These problems include economic and financial problems, business problems and firms operating problems. Besides, the study provides evidence about the impact of COVID-19 on revenue and employment within the firms of Pakistan.Furthermore, the study's findings would provide some guidelines about the problems that exist in the pandemic. Therefore, the government of Pakistan must take initiatives if any pandemic may appear. Finally, the study may provide the summarized insights into the economy of Pakistan, particularly concerning economics.